(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This work presents the experimental investigation of double effect evaporative cooling unit with approximate capacity 7 kW. The unit consisted of two stages, the sensible heat exchanger and the cooling tower composing the external indirect regenerative evaporative cooling stage where a direct evaporative cooler represent the second stage. Testing results showed a maximum capacity and lowest supplied air temperature when the water flow rate in heat exchanger was 0.1 L/s. The experiment recorded the unit daily readings at two airflow rates (0.425 m3/s, 0.48 m3/s). The reading shows that unit inlet DBT is effect positively on unit wet bulb effectiveness and unit COP at constant humidity ratio. The air extraction ratio effected positively on the unit wet bulb effectiveness within a certain limit where maximum COP recorded 11.4 when the extraction ratio equal to 40%.